THE EFFECTIVENESS OF THE USE OF PEDAGOGICAL TECHNOLOGIES IN TEACHING UROLOGICAL SUBJECTS - Mirzamakhmud A. Shadmanov (Central Asian Journal of Medicine, 2023)
The article deals with the pedagogical requirements for the organization of the didactic process in teaching clinical subjects using non-traditional methods, and also highlights the modern requirements for the transfer of urological knowledge to students based on pedagogical technologies.